2013
DOI: 10.1007/s10955-013-0874-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Phenomena in Exponential Random Graphs

Abstract: The exponential family of random graphs is one of the most promising class of network models. Dependence between the random edges is defined through certain finite subgraphs, analogous to the use of potential energy to provide dependence between particle states in a grand canonical ensemble of statistical physics. By adjusting the specific values of these subgraph densities, one can analyze the influence of various local features on the global structure of the network. Loosely put, a phase transition occurs wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Although much effort has been focused on 2-parameter models, k-parameter models have also been examined. As shown in [25], near degeneracy and universality are expected not only in generic 2-parameter models but also in generic k-parameter models. Asymptotically, a typical graph drawn from the "attractive" k-parameter exponential model where β 2 , .…”
Section: Introductionmentioning
confidence: 79%
“…Although much effort has been focused on 2-parameter models, k-parameter models have also been examined. As shown in [25], near degeneracy and universality are expected not only in generic 2-parameter models but also in generic k-parameter models. Asymptotically, a typical graph drawn from the "attractive" k-parameter exponential model where β 2 , .…”
Section: Introductionmentioning
confidence: 79%
“…Many people have delved into this area. A particularly significant discovery was made by Chatterjee and Diaconis [6], who showed that the supremum in (5.16) is always attained and a random graph drawn from the model must lie close to the maximizing set with probability vanishing in n. When β 3 , β 4 ≥ 0, Yin [35] further showed that the 3-parameter space would consist of a single phase with first-order phase transition(s) across one (or more) surfaces, where all the first derivatives of χ exhibit (jump) discontinuities, and second-order phase transition(s) along one (or more) critical curves, where all the second derivatives of χ diverge. The second special situation is when β 3 = 0, Following similar arguments as in Kenyon et al [17], we conclude that d(x) can take only finitely many values.…”
Section: Further Discussionmentioning
confidence: 99%
“…For a few mathematical results preceding [19], see [4,18]. For a nonexhaustive list of subsequent developments, see [2,3,30,31,[41][42][43][44][45][46]51]. The discussion in this section will be limited to a basic result from [19] and one easy example.…”
Section: Exponential Random Graphsmentioning
confidence: 99%